2016
DOI: 10.1038/srep38277
|View full text |Cite
|
Sign up to set email alerts
|

Melanosome transfer to keratinocyte in the chicken embryonic skin is mediated by vesicle release associated with Rho-regulated membrane blebbing

Abstract: During skin pigmentation in amniotes, melanin synthesized in the melanocyte is transferred to keratinocytes by a particle called the melanosome. Previous studies, mostly using dissociated cultured cells, have proposed several different models that explain how the melanosome transfer is achieved. Here, using a technique that labels the plasma membrane of melanocytes within a three-dimensional system that mimics natural tissues, we have visualized the plasma membrane of melanocytes with EGFP in chicken embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…This suggests that the expression of PtdSer on secreted melanosome clusters is a signal for recognition and phagocytosis by fibroblasts, in a similar manner as observed in ordinary exosomes. Another example is that PtdSer exposure was also observed in vesicles of membrane blebs containing a melanosome pinched off from melanocytes in chicken embryonic skin, and acts as a landmark for engulfment by neighboring keratinocytes [29]. These findings shed light on the notion that PtdSer-mediated endocytosis is utilized commonly in many events that occur in the skin.…”
Section: Discussionmentioning
confidence: 81%
“…This suggests that the expression of PtdSer on secreted melanosome clusters is a signal for recognition and phagocytosis by fibroblasts, in a similar manner as observed in ordinary exosomes. Another example is that PtdSer exposure was also observed in vesicles of membrane blebs containing a melanosome pinched off from melanocytes in chicken embryonic skin, and acts as a landmark for engulfment by neighboring keratinocytes [29]. These findings shed light on the notion that PtdSer-mediated endocytosis is utilized commonly in many events that occur in the skin.…”
Section: Discussionmentioning
confidence: 81%
“…Several models for the transfer mechanism have been proposed, and two of them have received more attention recently: the shedding of melanosome-loaded vesicles by melanocytes that are subsequently phagocytosed by keratinocytes and the exocytosis by melanocytes of melanosome cores or melanocores, which are then endo/phagocytosed by keratinocytes (Wu and Hammer, 2014). A recent study using chicken embryonic skin found evidence for the shedding/phagocytosis model (Tadokoro et al, 2016). On the other hand, we proposed that coupled exo/endocytosis of melanocores is the prevalent mechanism of melanin transfer present in human skin (Tarafder et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So far, different models of melanosome transfer have been proposed (Wu and Hammer, 2014). A recent study using live imaging of chicken embryonic skin revealed that melanosomes are transferred by vesicles derived from the melanocyte plasma membrane (Tadokoro et al, 2016).…”
Section: Molecular Mechanism Of Colorations: Melanin Non-melanin Chementioning
confidence: 99%